THE ROLE OG VILLAGE ASSISTANT IN OPTIMIZING THE DISTRIBUTION OF VILLAGE FUNDS IN GUNUNGCUPU CIAMIS DISTRICT: Peran Pendamping Desa dalam Mengoptimalkan Penyaluran Dana Desa di Gunungcupu Kabupaten Ciamis - Sulistiani; Nastiti Novitasari; Ahmad Hamdan (Jurnal Obor Penmas: Pendidikan Luar Sekolah, 2025)
The imbalance between the needs and availbility of village funds and the limited human resource of goverment staf, make it quite difficult for the village goverment to optimize the distribution of priority village funds. The presence of village assistants in one of the major supports for the goverment and the community in overcoming these problems. This study aims to determine the role played by village assistants in optimizing the distribution of village fund in Gunungcupu,Ciamis Regency. The reserch method used is a qualitative approach with thw descriptive method. The techniques used are observation, interviews and dosumentation. The result of the study show that there are several roles played by village assistants in optimizing the distribution of village funds in Gunungcupu, namely the role in conveying various matters related to village funds in village delibration forums and banners in strategic place, inventory problems together with the goverment and community by conducting survey in the field, openly provide consultation and education related to things that are not yet understood by the community and goverment both in the planning process to reporting, facilitate community groups that need training, conduct regular monitoring and evaluation of activities that have been funded by village funds. The conclusion of this study is that Gunungcupu Village assistants have attemted to provide assistance in the distribution of village funds through the role of socializing, identifying problems, providing consultation and education, conducting monitoring and evaluation. This is in accordance with the village assistant SOP.